2017
DOI: 10.21660/2017.35.60892
|View full text |Cite
|
Sign up to set email alerts
|

Field Performance of Transition Rigid Piled Embankment With Surcharged Vertical Drain Over Soft Ground

Abstract: Commonly, thick filling works over soft clay is aided with piled embankment at bridge approach to reduce differential settlement between the piled abutment and embankment over soft ground. However, long stretched thick filling works over soft ground requires substantial resources and time to construct rigid piled embankment. Generally for such long stretched and thick filling development over soft ground, other ground treatment such as prefabricated vertical drain (PVD) with surcharge is introduce to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A constitutive model was used to incorporate the effects of fabric anisotropy, structure and time. The numerical predictions were compared with field measurements and the results indicated that the creep model provides an improved approximation of field settlements; Ramli, Hossein, Puspanathan, and See-Sew in [5] conducted a case study in Tapin, South Kalimantan where two trial embankment sections were constructed using backfill materials transported from off-sites and from the local materials respectively. The result showed that the settlement under the embankment using the usual backfill material was bigger than the one with the combination of the local soil; in [6] a numerical modeling of the responses of Ballina test embankment was performed using an improved EVP-SANICLAY constitutive model with a novel rotational hardening (RH) law.…”
Section: Introductionmentioning
confidence: 99%
“…A constitutive model was used to incorporate the effects of fabric anisotropy, structure and time. The numerical predictions were compared with field measurements and the results indicated that the creep model provides an improved approximation of field settlements; Ramli, Hossein, Puspanathan, and See-Sew in [5] conducted a case study in Tapin, South Kalimantan where two trial embankment sections were constructed using backfill materials transported from off-sites and from the local materials respectively. The result showed that the settlement under the embankment using the usual backfill material was bigger than the one with the combination of the local soil; in [6] a numerical modeling of the responses of Ballina test embankment was performed using an improved EVP-SANICLAY constitutive model with a novel rotational hardening (RH) law.…”
Section: Introductionmentioning
confidence: 99%